Evaluation of the Effect of the Microscopic Glass Surface Protonation on the Hard Tissue Thin Section Preparation - Melinda Szalóki; Viktória Hegedűs; Tamás Fodor; Renáta Martos; Tünde Radics; Csaba Hegedűs; Balázs Dezső (Applied Sciences, 2020)
In this study, a new procedure for mounting tissue blocks was described while cutting and grinding the section remains tightly bound to the inert glass surface both chemically and micro mechanically allowing good quality specimens for staining and microscopic analysis. The micromechanical interlocking was achieved by using of frosted glass, the chemical binding was made with 10-methacryloyloxydecyl dihydrogen phosphate monomer (10-MDP) containing bond material. The glass surface activation was achieved by nitric acid etching and the surface was characterized by zeta potential, X-ray photoelectron spectroscopy (XPS), and contact angle measurements. Cylindrical samples were prepared from epoxy embedding materials, cortical bovine bone, and dental titanium to investigate the shear bond strengths (SBS) to microscopic glass slide compared to a routinely used thermoplastic adhesive. Based on the experiments it was found that the micromechanical retention combined with MDP containing bond material improved the SBS data compared to the thermoplastic adhesive. The acid etched glass became positively charged that significantly increased the SBS data of bone and titanium compared with the uncharged version. Therefore, the thickness of the undecalcified bone section with metal can safely reduce to improve histological microscopic analysis.